Keberagaman Bumi Dan Ekonomi Dalam Surah Ar-Rad Ayat 4 - Fahnisa, Fahnisa; Tarigan, Azhari Akmal; Syahriza, Rahmi (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
The diversity of adjacent land referred to here is how on earth there are parts of land that are side by side but have different characteristics. even though the lands are close together, they can produce crops that differ in taste and type. It shows the natural wonders and diversity that exist on earth. This concept is found in the Al-Quran Surah Ar-Rad verse 4 and this verse implies the existence of soil science (geology and geophysics) and environmental science (ecology) and their influence on the properties of plants. It is scientifically known that rice field soil consists of mineral grains of various sources, sizes and composition, water that comes from rain, air, organic substances that come from plant waste and other living creatures that are above or in the layers. land. To overcome these problems, it is necessary to have a concept of integration between religion and science in the Islamic world. This research is library research, using a descriptive approach method. The data used was obtained from primary data in the form of the Al-Qur'an and hadith interpretations. And secondary literature data that supports the primary research.